Birth outcomes in women with gestational diabetes managed by lifestyle modification alone: The PANDORA study. (November 2019) - Cheng, E.; Longmore, D.K.; Barzi, F.; Barr, E.L.M.; Lee, I.L.; Whitbread, C.; Boyle, J.A.; Oats, J.; Connors, C.; McIntyre, H.D.; Kirkwood, M.; Dempsey, K.; et al.
Abstract: Aims: To assess outcomes of women in the Pregnancy and Neonatal Diabetes Outcomes in Remote Australia (PANDORA) cohort with gestational diabetes mellitus (GDM) managed by lifestyle modification compared with women without hyperglycaemia in pregnancy. Methods: Indigenous (n = 97) and Europid (n = 113) women managed by lifestyle modification were compared to women without hyperglycaemia (n = 235). Multivariate linear and logistic regressions assessed whether GDM-lifestyle women had poorer outcomes compared to women without hyperglycaemia. Results: Women with GDM-lifestyle had higher body mass index and lower gestational weight gain than women without hyperglycaemia. On univariate analysis, gestational age at delivery was lower and induction rates were higher in women with GDM-lifestyle than without hyperglycaemia. On multivariable regression, GDM-lifestyle was associated with lower gestational age at delivery (by 0.73 weeks), lower birthweight z-score (by 0.26, p = 0.007), lower likelihood of large for gestational age (LGA) [OR (95% CI): 0.55 (0.28, 1.02), p = 0.059], and greater likelihood of labour induction [2.34 (1.49, 3.66), p < 0.001] than women without hyperglycaemia. Conclusion: Women with GDM managed by lifestyle modification had higher induction rates and their offspring had lower birthweight z-scores, with a trend to lower LGA than those without hyperglycaemia in pregnancy. Further studies are indicated to explore reasons for higher induction rates.